2018
DOI: 10.1186/s10033-018-0212-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Shape Control for Thermal Deformation of Membrane Mirror with In-plane PVDF Actuators

Abstract: Optical membrane mirrors are promising key components for future space telescopes. Due to their ultra-thin and high flexible properties, the surfaces of these membrane mirrors are susceptible to temperature variations. Therefore adaptive shape control of the mirror is essential to maintain the surface precision and to ensure its working performance. However, researches on modeling and control of membrane mirrors under thermal loads are sparse in open literatures. A 0.2 m diameter scale model of a polyimide mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A plate membrane model and a pure membrane model have been studied respectively to achieve active vibration control of plate membrane mirrors [20]. A closed-loop membrane mirror shape control system is set up and a surface shape control method based on an influence function matrix of the mirror is then investigated [21]. To analyze the nonlinear dynamic characteristics of the membrane, the theoretical and approximate solutions of nonlinear frequencies of the membrane are obtained, and the discrepancies between the two solutions under different vibration amplitudes are discussed [22].…”
Section: Schematic Of Membrane Subjected a Central Concentrated Loadmentioning
confidence: 99%
“…A plate membrane model and a pure membrane model have been studied respectively to achieve active vibration control of plate membrane mirrors [20]. A closed-loop membrane mirror shape control system is set up and a surface shape control method based on an influence function matrix of the mirror is then investigated [21]. To analyze the nonlinear dynamic characteristics of the membrane, the theoretical and approximate solutions of nonlinear frequencies of the membrane are obtained, and the discrepancies between the two solutions under different vibration amplitudes are discussed [22].…”
Section: Schematic Of Membrane Subjected a Central Concentrated Loadmentioning
confidence: 99%
“…The results showed that PVDF/PEDT/PANI-ND nanocomposite have promising perspectives in Li-ion batteries. 7,15,32…”
Section: Samplementioning
confidence: 99%
“…Because of biocompatibility, flexibility, strength, conductivity, piezoelectric, and pyroelectric properties, PVDF-based nanocomposites have been found suitable for biomedical devices, lithium (Li) batteries, microelectronic devices, actuators, and energy harvesters. [5][6][7][8] Among a wide range of conducting polymers, polyaniline (PANI), polypyrrole, polythiophene, and polyphenylene are important. Mostly, conducting polymers are insoluble in common solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of propeller hydrodynamic force, non-uniform wake excitation, machining accuracy and assembly accuracy, lateral vibration generated by propulsion shafting will be transmitted to the hull structure, thus producing underwater acoustic radiation [1][2][3]. The active control method implemented by actuators exhibit good performance on mechanical vibration control [4][5][6][7]. As the shafting system belongs to equipment with large mass and high stiffness, it is required that actuators with high mass power ratio are needed to conduct lateral vibration control of propulsion shafting [8].…”
Section: Introductionmentioning
confidence: 99%